Pengaruh Cash Conversion Cycle Terhadap Return On Assets Perusahaan Makanan Dan Minuman Di Bei 2021–2025 - Alfina Achma Ramadhani; Cici Kurnia Nur Cholifah; Istiono Istiono (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the effect of Cash Conversion Cycle (CCC) on Return on Assets (ROA) in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2021–2025. CCC is a working capital efficiency indicator reflecting the time required for a company to convert its operational investment into cash. ROA is used as a profitability proxy as it represents the effectiveness of asset utilization. A quantitative associative approach was employed using balanced panel secondary data comprising six companies over five years, yielding 30 observations. Samples were selected through purposive sampling, including INDF, ROTI, GOOD, ULTJ, CAMP, and SKLT. Simple linear regression with classical assumption tests was applied. Results show that CCC does not significantly affect ROA (t = 1.127; p = 0.269 > 0.05) with an R² of 0.043. The regression coefficient of CCC is positive (β = 0.000256), contrary to the hypothesized negative direction. This finding suggests that profitability in food and beverage companies during the study period is more influenced by other factors beyond working capital efficiency, such as business scale, product margins, and distribution strategies. This study contributes additional empirical evidence in Indonesia on the CCC-ROA relationship in the food and beverage sub-sector.